Novel crAssphage marker genes ascertain sewage pollution in a recreational lake receiving urban stormwater runoff. (15th November 2018) - Ahmed, Warish; Payyappat, Sudhi; Cassidy, Michele; Besley, Colin; Power, Kaye
Abstract: Considerable efforts have been made in recent years in developing novel marker genes for fecal pollution tracking in environmental waters. CrAssphage are recently discovered DNA bacteriophage that are highly abundant in human feces and untreated sewage. In this study, we evaluated the host-sensitivity and -specificity of the newly designed crAssphage qPCR assays (Stachler et al., 2017 ) CPQ_056 and CPQ_064 (i.e., marker genes) in fecal samples collected from various human and several animal host groups in Australia. We also investigated the utility of these marker genes to detect sewage pollution in an urban recreational lake (i.e., Lake Parramatta) in Sydney, NSW. The mean concentrations of CPQ_056 and CPQ_064 marker genes in untreated sewage were 9.43 ± 0.14 log10 GC/L and 8.91 ± 0.17 log10 GC/L, respectively, 2 to 3 orders of magnitude higher than other sewage-associated viruses used in microbial source tracking studies. Among 177 animal fecal samples tested from 11 species, the host-specificity values for CPQ_056 and CPQ_064 marker genes were 0.95 and 0.93, respectively. Limited cross-reactivity was observed with cat fecal and cattle wastewater samples. Abundance of crAssphage markers were monitored in an urban lake that receives stormwater runoff. The concentrations of both markers were higher (CPQ_056 ranging from 3.40 to 6.04 log10 GC/L and CPQ_064 ranging from 2.90 to 5.47 log10 GC/L) in 20 of 20 (for CPQ_056) and 18 of 20 (for CPQ_064) samples collected after storm events with gauged sewer overflows compared to dry weather event (10 of 10 samples were qPCR negative for the CPQ_056 and 8 of 10 were negative for the CPQ_064 marker genes) suggesting sewage pollution was transported by urban stormwater runoff to Lake Parramatta. The results of the study may provide context for management of sewage pollution from gauged overflow points of the sewerage system in the catchment. Highlights: Host-specificity values of crAssphage marker genes were >0.90. CrAssphage marker genes showed limited cross-reactivity with cat and cattle feces. High abundance of crAssphage markers were detected in an urban lake used for swimming.